Probing myelin and axon abnormalities separately in psychiatric disorders using MRI techniques - Ongur, Dost; Du, Fei (Frontiers in Integrative Neuroscience, 2013)
In this manuscript we present novel MRI approaches to dissecting axon vs. myelin abnormalities in psychiatric disorders. Existing DTI approaches are not able to provide specific information on these subcellular elements but novel approaches are beginning to do so. We review two approaches (magnetization transfer ratio—MTR; and diffusion tensor spectroscopy—DTS) and the theoretical framework for interpreting data derived from these approaches. Work is ongoing to collect data that will answer some relevant questions using these techniques in schizophrenia and related conditions.